Clinical Applications of Hyperpolarised Xenon-129 MRI - Kher Lik Ng; James Grist; Fergus Gleeson; Emily Fraser (European Medical Journal)
Conventional imaging modalities, the X-ray and CT, are essential diagnostic tools in respiratory medicine, providing qualitative information regarding the pattern and extent of pulmonary pathology. Neither provide information regarding the functional impact of pulmonary diseases and additional investigations are required to assess this. Hyperpolarised xenon-129 MRI (HPX-MRI) is a non-invasive, ionising-free imaging modality that can provide functional measurements of ventilation and diffusion within the lung. The MRI-based technique involves the subject breathing in an inert gas that has been hyperpolarised to make it visible using MR spectroscopy. The gas mirrors the flow of oxygen through the bronchial tree, across the alveolar membrane, and into the pulmonary capillaries, and thus disruptions in the passage of gas due to ventilation and diffusion abnormalities can be visualised and quantified. Functional measurements of ventilation and gas exchange within regional areas of the lung can be obtained. HPX-MRI has the potential to detect early lung disease not yet evident using standard investigations and has been shown to be a sensitive modality to assess treatment responses. The role of HPX-MRI in respiratory medicine has the potential to be wide-reaching, but to date it remains largely a research tool. This review article summarises the current and possible future clinical applications of HPX-MRI in the investigation and management of lung diseases, pitched at a level comprehensible and relevant to the respiratory-focused clinicians.